The Movement and Exchange of Dogs in the Prehistoric Caribbean: An Isotopic Investigation. (18th April 2013) - Laffoon, J. E.; Plomp, E.; Davies, G. R.; Hoogland, M. L. P.; Hofman, C. L.
Abstract This study explores the feasibility of using strontium isotope (87Sr/86Sr) analyses of enamel from domestic dogs (Canis familiaris) to investigate networks of exchange in the prehistoric Circum‐Caribbean. Dog teeth were obtained from burial and domestic contexts from two prehistoric sites (Anse à la Gourde and Morel) on Grande‐Terre, Guadeloupe (Lesser Antilles). Strontium isotope results were compared with local biosphere 87Sr/86Sr data at the scale of the site, island and archipelago. The isotope results indicate both local and nonlocal origins with three dogs (30%) identified as nonlocal (one from Anse à la Gourde and two from Morel). The variance in 87Sr/86Sr ratios of the nonlocal dog teeth is consistent with diverse multiple origins external to the island of Grande‐Terre but consistent with origins from other islands of the Lesser Antilles. The diverse origins of the nonlocal dog samples indicate that the prehistoric circulation of dogs occurred at multiple scales from regional to long distance. Significantly, the 87Sr/86Sr ratios of some of the dog teeth are comparable with values of nonlocal humans at Anse à la Gourde determined in previous studies. It is possible that these comparable 87Sr/86Sr ratios result from similar natal origins, for example if individuals were migrating to Guadeloupe with dogs. The results of this study contribute to an ongoing regional investigation of the economic, social and political roles of animals and animal remains and the multiscalar networks of prehistoric mobility and exchange in the Circum‐Caribbean region. Copyright © 2013 John Wiley & Sons, Ltd.